Comparative study of virulence potential, phylogenetic origin, CRISPR-Cas regions and drug resistance of Escherichia coli isolates from urine and other clinical materials - Dziuba, Anna; Dzierżak, Sylwia; Sodo, Anna; Wawszczak-Kasza, Monika; Zegadło, Katarzyna; Białek, Jakub; Zych, Natalia; Kiebzak, Wojciech; Matykiewicz, Jarosław; Głuszek, Stanisław; Adamus-Białek, Wioletta (Frontiers in Microbiology, 2023)
Urinary tract infections (UTI), among which the main etiological factor is uropathogenic Escherichia coli (UPEC, E. coli), remain an important issue for clinicians. The aim of the study was to demonstrate clear differences in the pathogenic properties of urine-derived E. coli compared to other extraintestinal E. coli clinical isolates (derived from: blood, lower respiratory tracts, sputum, reproductive tract, body fluids, perianal pus, other pus, wound, postoperative wound and other sources). The collection of 784 E. coli isolates was collected from various materials of hospitalized patients. They were analyzed in terms of virulence-associated genes (papC, sfaD/sfaE, cnf1, usp, fimG/H, hlyA), belonging to phylogenetic groups and the presence of CRISPR-Cas regions using PCR. In addition, the epidemiological data and the antibiotic resistance profiles provided by the hospital's microbiology department were included for statistical analyses. Urine-derived E. coli showed significantly greater virulence potential compared to other isolates, but they were generally unremarkable in terms of drug resistance. The isolates most often belonged to phylogenetic group B2. Drug resistance was negatively correlated with CRISPR 2 presence and high average virulence score, but positively correlated with CRISPR 4 presence. To the best of our knowledge, we are the first to report significant differences in sputum-derived isolatesthey revealed the lowest virulence potential and, at the same time, the highest drug resistance. In conclusion, we demonstrated significant differences of urinary-derived E. coli compared to other clinical E. coli isolates. We would like to suggest excluding penicillins from use in E. coli infection at this time and monitoring strains with a high pathogenicity potential.